P14.24 Multicultural survey – asian female sex worker demographics, migration and sexual health in sydney. (13th September 2015) - Martin, L; Thng, C; Wand, H; McNulty, A; Foster, R; McGregor, S
Abstract : Theme: Social policy, behavioural change, psychosocial or psychosexual issues related to sexual health. Background: Sydney Sexual Health Centre (SSHC) provides dedicated clinics, outreach services and bilingual health education staff to Chinese and Thai sex workers. We aimed to assess characteristics of these sex workers. Methods: A cross-sectional survey was conducted between August 2014–March 2015 using a structured questionnaire in Thai and Chinese, offered to female sex workers attending SSHC and within parlours visited by outreach staff. Results: 338 participants were recruited: 106(32%) Chinese and 232(68%) Thai. Overall median age was 31 years. More than half (56%) did not attend high school, with Chinese participants less likely to have attended high school than Thai (67% vs 50%; p = 0.003). Compared with those attending the clinic, women seen on outreach were older (42% >35 vs 20% from clinic; p = 0.00) and less likely to have done sex work previously (90% vs 71% from clinic; p = 0.00). Compared to Thai, Chinese participants were more likely to report "poor" English skills in speaking (61% vs 27% Thai), reading (70% vs 31% Thai) and writing (78% vs 39% Thai) (p < 0.001). While the majority of participants were not on a sex work contract (92%), those who were contracted were more likely to be Thai (10% vs 3% Chinese; p = 0.017). Significantly more Thai participants worked in massage (n = 84, 36%) compared with Chinese (n = 16, 15%) (p < 0.001) Chinese participants were more likely to check clients for signs of STIs (n = 75, 70% vs Thai n = 115, 50%; p < 0.001), less likely to douche (n = 17, 16% vs Thai n = 112, 48%; p < 0.001), and had fewer misconceptions about STI transmission via unprotected oral sex (n = 64, 60% vs Thai n = 179, 77%; p = 0.001). Conclusion: There were significant differences in the characteristics and behaviours of Thai and Chinese sex workers surveyed. Essential education within culturally appropriate health promotion programs should include douching, checking clients for STIs and using condoms for oral sex. Disclosure of interest statement: No conflict of interest.